2017
DOI: 10.11648/j.ajns.20170602.13
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life Among Girls with or Without Clinically Significant Premenstrual Syndrome

Abstract: Premenstrual syndrome (PMS) is one of the most vague and ill-defined phenomena in the field of woman health.Almost all its definitions concluded that it is a cyclic recurrence of distressing physical, psychological and behavioral symptoms, that occur during the luteal phase of menstrual cycle and evaporates within two days of the onset of menses. PMS may range in its severity from mild (90% of females) to moderate or severe (12.6-31% of females). The last type is called Clinically Significant Premenstrual Synd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…Studies in Korea have shown that PMS prevalence was 36.1% in adolescents and 38.1% in women of childbearing age (14), while its prevalence was 98.1% to 100% in female college students (15). In a study by Tsai et al (16) on a population of female employee in Taiwan, the prevalence of the symptoms of PMS was reported to be 24% for fatigue, 21.2% for headache and 17.4% for abdominal bloating.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in Korea have shown that PMS prevalence was 36.1% in adolescents and 38.1% in women of childbearing age (14), while its prevalence was 98.1% to 100% in female college students (15). In a study by Tsai et al (16) on a population of female employee in Taiwan, the prevalence of the symptoms of PMS was reported to be 24% for fatigue, 21.2% for headache and 17.4% for abdominal bloating.…”
Section: Introductionmentioning
confidence: 99%
“…In Korea, the prevalence of PMS is 36.1% and 38.1% in adolescents and women of childbearing age, respectively, and among them, 12.3% and 8.8% of women report experiencing severe symptoms [10]. Other studies found that 100% of nursing students and 98.1% of general female college students reported experiencing premenstrual syndrome, with various prevalence rates depending on the diagnostic method or population [11,12] Female college students, who have a relatively high prevalence compared to other age groups, have reported that PMS is associated with poor academic accomplishment, low quality of life, difficulty in maintaining social activities, a higher level of daily stress, and even criminal behavior and suicidality [13][14][15][16][17]. Previous research suggests that 11.8% of female students and 1.7% of those with moderate PMS showed symptoms of significant depression, respectively [18].…”
Section: Introductionmentioning
confidence: 99%